2021
DOI: 10.1016/j.tibs.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial compartmentalization: emerging themes in structure and function

Abstract: Within cellular structures, compartmentalization is the concept of spatial segregation of macromolecules, metabolites, and biochemical pathways. Therefore, this concept bridges organellar structure and function. Mitochondria are morphologically complex, partitioned into several subcompartments by a topologically elaborate two-membrane system. They are also dynamically polymorphic, undergoing morphogenesis events with an extent and frequency that is only now being appreciated. Thus, mitochondrial compartmentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 139 publications
1
37
0
Order By: Relevance
“…In line with this assumption, IP-purification proteomics revealed that PLIN5-mediated LDMC promoted significant interactions with several NADH-ubiquinone oxidoreductase proteins from respiratory complex I and other proteins involved in OXPHOS and mitochondrial dynamics, which were abrogated upon disrupted LDMC. Strikingly, we also observed PLIN5 interaction with several members of the mitochondrial contact site and cristae organizing system complex that plays a critical role in the formation and remodeling of mitochondrial cristae, which encompass the majority of OXPHOS complexes ( 44 , 45 ). Particularly interesting, Varghese et al.…”
Section: Discussionmentioning
confidence: 75%
“…In line with this assumption, IP-purification proteomics revealed that PLIN5-mediated LDMC promoted significant interactions with several NADH-ubiquinone oxidoreductase proteins from respiratory complex I and other proteins involved in OXPHOS and mitochondrial dynamics, which were abrogated upon disrupted LDMC. Strikingly, we also observed PLIN5 interaction with several members of the mitochondrial contact site and cristae organizing system complex that plays a critical role in the formation and remodeling of mitochondrial cristae, which encompass the majority of OXPHOS complexes ( 44 , 45 ). Particularly interesting, Varghese et al.…”
Section: Discussionmentioning
confidence: 75%
“…Compartmentalization serves a function as specific bioenergetic processes are performed within the matrix, for instance the tricarboxylic acid cycle (TCA) or the beta-oxidation of fatty acids (FAs). Within the matrix also lie mitochondrial DNA and ribosomes where transcription and translation of the few mitochondrially encoded proteins occur [ 6 , 13 ].…”
Section: Mitochondrial Membrane Physiology and Lipid Compositionmentioning
confidence: 99%
“…The IMS has a much more complex and, as of today, much more elusive role. Protein sorting, redox balancing with glutathione oxidation and reduction, and most importantly, cytC release and apoptotic cascade activation, are some of the many functions regulated by the extremely confined, only 5% of mitochondrial space, IMS [ 6 , 13 , 14 ]. IMS itself is physically and functionally subdivided into at least two different compartments, the peripheral intermembrane space and the intracristae space (ICS) [ 15 ].…”
Section: Mitochondrial Membrane Physiology and Lipid Compositionmentioning
confidence: 99%
“…These alteration in ROS levels, mtDNA release and membrane potential could be related with mitochondrial structural modifications as was observed during apoptosis (57,58). To analyze the mitochondrial ultra-structure, we performed the correlative light-electron microscopy (CLEM) study in 23132/87 cell lines expressing the GSDMB-NT GFP inducible constructions (1-220 or 1-242) that co-localized with mitoTracker Deep Red marker (Figure 2E).…”
Section: Gsdmb Nt-induced Cell Death Associates With Mitochondrial Da...mentioning
confidence: 85%